2009
DOI: 10.1161/circimaging.108.811273
|View full text |Cite
|
Sign up to set email alerts
|

Alteration in Left Ventricular Strains and Torsional Mechanics After Ultralong Duration Exercise in Athletes

Abstract: Background-Numerous studies have reported evidence of cardiac injury associated with transient left ventricular (LV) systolic and diastolic dysfunction after prolonged and strenuous exercise. We used 2D ultrasound speckle tracking imaging to evaluate the effect of an ultralong-duration exercise on LV regional strains and torsion. We speculated that systolic dysfunction after exercise is associated with depressed LV strains and torsion, and diastolic dysfunction results from decreased and delayed untwisting, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
89
7
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(110 citation statements)
references
References 50 publications
13
89
7
1
Order By: Relevance
“…At midrace (148 km; 47 Ϯ 7 h), SV was greater than at prerace, an observation in accordance with one of our previous studies after 38 h of running (39). Conversely, after shorter-duration exercises, SV was generally decreased (26,29,35,42). Of note, consequently to the higher SV, we observed a greater cardiac output at mid-and posttest.…”
Section: Discussionsupporting
confidence: 91%
“…At midrace (148 km; 47 Ϯ 7 h), SV was greater than at prerace, an observation in accordance with one of our previous studies after 38 h of running (39). Conversely, after shorter-duration exercises, SV was generally decreased (26,29,35,42). Of note, consequently to the higher SV, we observed a greater cardiac output at mid-and posttest.…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the discovery that IEET leads to an increase in LVtw might appear to contradict some prior studies (5,32). The lack of an athletic background of our study participants and the longitudinal study design might explain these results.…”
Section: Left Ventricular Twistingcontrasting
confidence: 90%
“…In contrast to this study, the present study, which featured longitudinal follow-up, did not include layer specific analysis. However, in some studies, the athletes' LV strain measurements were found to be similar to control groups (5,26). The seemingly discordant results may be explained by several factors, including study population (subject number), study design (longitudinal or case-control), athletic experience and strain measurements that might be affected by loading conditions.…”
Section: Left Ventricular Systolic Functions and Left Ventricular Strainmentioning
confidence: 96%
See 2 more Smart Citations